2016
DOI: 10.1155/2016/4851454
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of Steady Cavitating Flow in a Small Francis Turbine

Abstract: The turbulent flow through a small horizontal Francis turbine is solved by means of Ansys-CFX at different operating points, with the determination of the hydrodynamic performance and the best efficiency point. The flow structures at different regimes reveal a large flow eddy in the runner and a swirl in the draft tube. The use of the mixture model for the cavity/liquid two-phase flow allowed studying the influence of cavitation on the hydrodynamic performance and revealed cavitation pockets near the trailing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 29 publications
1
4
0
1
Order By: Relevance
“…This can cause a change in the flow pattern, leading to loss of efficiency, in addition to the increase in vibration. It was observed that in the region of the blade suction, there is the presence of a high velocity gradient and these outcomes are also described in a similar case by [29], in his study on small Francis turbines with low flow rates. The visualization of this region is important due to the fact that these vortices creates low pressure regions, and the phenomenon of cavitation may occur.…”
Section: Performance Of the Indalma Hydro-turbinesupporting
confidence: 55%
“…This can cause a change in the flow pattern, leading to loss of efficiency, in addition to the increase in vibration. It was observed that in the region of the blade suction, there is the presence of a high velocity gradient and these outcomes are also described in a similar case by [29], in his study on small Francis turbines with low flow rates. The visualization of this region is important due to the fact that these vortices creates low pressure regions, and the phenomenon of cavitation may occur.…”
Section: Performance Of the Indalma Hydro-turbinesupporting
confidence: 55%
“…It is found out that sliding mesh approach does not offer significant advantage when compared to the frozen rotor model based on comparisons with each other and experimental data. Laouari and Ghenaiet [18] used frozen rotor interface to simulate the turbulent flow through a small horizontal Francis turbine. Hydraulic performance is presented for different rotational speeds.…”
Section: Methodsmentioning
confidence: 99%
“…Una de las formas de analizar los daños superficiales que causa la cavitación es realizando la simulación numérica de un modelo utilizando un software de análisis de dinámica de fluido CFD (Computational Fluid Dynamics) para analizar los efectos de la variación de la velocidad del fluido, carga y presión sobre las partes del rodete. Para que el modelo sea considerado válido, los resultados numéricos deben ser comparados con mediciones experimentales [11], [12], [13].…”
Section: Análisis Numérico De Los Efectos De Launclassified